Takotsubo syndrome in the context of atherosclerotic acute myocardial infarction: the role of magnetic resonance imaging in determining cause or consequence - Cristhian Espinoza Romero; Vinícius Machado Correia; Williams Lata; Kevin De Paula Morales; Lenny Borja Valdivieso; Gabriela Ottoni Pin; Tatiana Torres Leal (Exploration of Cardiology)
We present the case of a woman admitted for an acute ST-segment elevation myocardial infarction. Emergency catheterization was conducted, revealing diffuse lesions affecting 70% of the anterior descending artery from the mid to the distal third but with ventriculography compatible with Takotsubo syndrome. Two magnetic resonances were performed 90 days apart, confirming the unusual coexistence of Takotsubo syndrome and transmural infarction in the same event.